Efectos de un programa educativo investigativo sobre habilidades de investigación en estudiantes del cuarto nivel de la especialidad en filosofía y psicopedagogía de la UNAP, Iquitos 2019 - Ríos Guedez, Manuel Olinto (2022)
The thesis Educational Research Program, to Strengthen Research Skills in Students of the fourth level of the specialty in Philosophy and Psychology of the UNAP, Iquitos 2019, Evaluative Research, used a quasi-experimental design and was aimed at evaluating the effect of the Program educational research in 30 students of the fourth level, already mentioned that made up the experimental group, to then compare them with the 30 students of the control group. According to the analyzed and contrasted results, it is concluded that the Investigative educational program produces positive effects in the strengthening of investigative skills in Fourth Level Students of the Faculty of Education Sciences and Humanities. ONE P. 2021. Because there is a significant difference between the pretest (15, 14) and the posttest (18, 34), which indicates the positive effect of the educational program. In conclusion, the educational program significantly strengthens the investigative skills in students of the fourth level of psychology and philosophy of the Faculty of Education Sciences and Humanities, due to the fact that there is a significant difference between the pretest (15,14) and the posttest (18,34), which indicates the effectiveness of the educational program in strengthening investigative skills.